The world in the mind and sculpture of deafblind people - Niestorowicz, Ewa Anna (Cambridge Scholars Publishing, 2017)
The World in the Mind and Sculpture of Deafblind People discusses the creative capabilities of people with simultaneous impairment of sight and hearing. It is a pioneering interdisciplinary study combining theories from the fields of pedagogy, psychology, semiotics and theory of art. It presents a study of the act of creation performed by deafblind people, which makes it possible to propose a vision of reality as conveyed through their sculptures, and which forms a base for the scrutiny of the specific and individual ways of understanding the world and its visualisation in the minds of deafbli.